Stability analysis of generalized second-order nonlinear control systems - Wang, Cong; Li, Li; Yao, Minghui; Wu, Qiliang; Niu, Yan (Journal of the Franklin Institute, 2025)
To overcome the constant boundedness and slow time-varying constraints of disturbances, this paper presents a generalized second-order nonlinear control algorithm (GSONCA) and resulting a generalized second-order nonlinear control system (GSONCS), and further studies the stability and disturbance rejection of GSONCS. Unlike existing similar works, the GSONCS is a universal second-order system framework including nonlinear, time-varying, and switching terms, which is able to deal with time-dependent and state-dependent disturbances. All possible equilibrium points are discussed for the GSONCS, and the existence condition of a unique equilibrium point is constructed. Several practical stability inequalities of coefficients are established for the GSONCS where the coefficients can be almost arbitrary functions of state variable and time, which unify the stability criterion of second-order linear and nonlinear systems. Based on the proposed stability results, the disturbance rejection conditions of GSONCS are derived, and the good robustness of state-dependent-type second-order nonlinear systems is confirmed. As the applications of GSONCS, the parameter tuning methods of popular second-order algorithms are provided, and simulations on DC-DC converters are presented to validate the proposed GSONCA.